Introduction: Literary Journalism as a Discipline - Bak, John S.; Martinez, Monica (Brazilian journalism research, 2018)
The editors of this issue of Brazilian Research Journalism welcome that debate, firmly believing that nothing new emerges without dialogue, from outside and inside the discipline. After all, literary and journalistic studies are not haunted by their many, at times antagonistic, schools of critical thought. On the contrary, both are made richer by them. As the Brazilian adage goes: “In the struggle of the sea against the cliff, none suffers but the shellfish.” And yet, the shellfish not only survives that eternal battle; it also thrives and prospers. This volume thus hopes that any debate that it generates will ultimately serve literary journalism studies in establishing itself as a discipline unique to itself, but always open and willing to foster a dialogue with other fields of knowledge.